Comparison between mixed reality with artificial algorithms and ultrasound in localization of anterior thigh flap perforators: a prospective randomized controlled study - Yixiu Liu; Wanlin Fan; Miao Yu; Jian Wu; Shuangjiang Wu; Lian Zhou; Qi Chen (BMC Medicine)
Abstract Background This study explores the efficacy of integrating mixed reality (MR) technology with artificial algorithms for locating vessels during anterolateral thigh perforator flap surgeries, comparing it with color Doppler ultrasonography (CDU) to provide clinical insights. Methods Eighty patients were randomly assigned to the MR group or the CDU group, with 40 patients in each. In the MR group, a localization device was attached to the lower limb, and CT angiography (CTA) data were converted into a 3D model. An artificial algorithm matched the device with the 3D model to overlay perforating vessels. The CDU group used traditional preoperative localization. Primary outcomes included the number of identified perforators and the distance between marked and actual vessel exit points. Secondary outcomes were flap harvest time and flap survival. Results Recognition rates were 94.3% in the MR group and 82.0% in the CDU group (P = 0.008). The average distance between marked and actual exit points was 1.5 mm vs. 2.7 mm (P < 0.0001). Flap harvest times averaged 52 and 68 min, respectively (P < 0.0001). In the MR group, one flap developed an infection and another necrosis, while in the CDU group, one flap had a crisis, and two experienced necrosis. Conclusions Mixed reality combined with artificial algorithms offers superior vessel localization compared to ultrasound and holds promise for multidisciplinary perforator flap surgeries. Trial registration This study was approved by the Ethics Committee of Chongqing University Cancer Hospital (Ethical Approval Number: CZLS2021177-A) and retrospectively registered at the Chinese Clinical Trial Register (registration number: CHiCTR2400087615, date of registration: 2024–07-31).